Analisis Pengaruh Simultan dan Parsial Lingkungan Kerja, Disiplin Kerja, Dan Kerjasama Tim Terhadap Kinerja Karyawan Di PT. Ghita Avia Trans - Eva Meilia; Supardi Supardi (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This scientific research aims to examine the impact of work environment, work discipline, and team collaboration on employee performance at PT. Ghita Avia Trans, both in aggregate and in isolation. The methodological framework used in this study is a quantitative approach, utilizing multiple linear regression analysis facilitated by SmartPLS 3 analytical software. The population for this study consisted of 90 employees, from whom a complete enumeration was conducted through a saturated sampling technique. Data acquisition was conducted through a questionnaire administered through Google Forms, using a five-point Likert scale for measurement. The findings indicate that individually, work environment, work discipline, and team collaboration have a positive and statistically significant influence on employee performance. Collectively, these three variables also show a substantial effect on improving employee performance at PT. Ghita Avia Trans. These results underscore the importance of fostering a supportive work environment, enhancing discipline, and strengthening team collaboration to facilitate optimal performance within an organization.